Mediating Role of Family Ownership in Relationship between the Independent Board and the Company’s Performance in Tehran Stock Exchange - Haghjoo, Sam Darvish; Moghadam, Abdolkarim; Mousavi, Seyed Ahmad (International Journal of Economics and Financial Issues, 2017)
This study examines the role of moderator family-owned in the relationship between the independent board and company’s performance in the Stock Exchange of Tehran. In this study return on assets and independent board are as dependent variables, family ownership and the interaction between the independent board and family ownership as independent variables The statistical society that is considered in this survey is all the accepted companies in Tehran’s Stock Exchange are in the studied years and read conditions. Due to the fact that before estimating and performing the regression models, it’s needed to make sure of some of the conditions among the variables. These conditions are normality, heteroscedasticity, self-correlation, collinearity, stationary of variables. The inferential statistics used in this research include multivariable regression, in order to discover the relationships of dependent and independent variables. By the way to make sure that the results are reliable, default regression tests have been used. Finally with approval of all default regression tests, they started to test the research’s hypothesis. The results showed that family ownership adjust the relationship between board independence and firm performance. Also there is a negative relationship between family-owned and independent board company. Keywords: Family Ownership, Board Independence, Firm Performance JEL Classifications: G31, L25